Last Exit : Privatization and Deregulation of the U.S. Transportation System - Winston, Clifford, 1952- (Book collections on Project MUSE., 2010)
"Proposes experiments in deregulating and privatizing the country's transportation systems to rid them of inefficiencies and significantly improve their performance in moving goods and people around the United States; the book covers roads, airports and airport traffic control, mass transit, intercity buses and railway networks"--Provided by publisher